A new species of viviparous brotula genus Pseudogilbia (Ophidiiformes: Dinematichthyidae) from Brazilian reefs, with an updated diagnosis of the genus. Issue 4 (12th August 2021) - Bauer, Arthur B.; Schwarzhans, Werner W.; Moura, Rodrigo L.; Nunes, José Anchieta C. C.; Mincarone, Michael M.
Abstract: In this study, a new species of Pseudogilbia Møller, Schwarzhans & Nielsen 2004 is described based on two male specimens (40–44 mm L S ) from shallow reefs of Bahia, Brazil. Pseudogilbia australis sp. nov. is distinguished from its only congener, Pseudogilbia sanblasensis Møller, Schwarzhans & Nielsen 2004 from Caribbean Panama, by having: two lower preopercular pores ( vs . one); dorsal‐fin rays 65–67 ( vs . 69); anal‐fin rays 51–53 ( vs . 56); pectoral‐fin rays 18 ( vs . 20); caudal vertebrae 27–28 ( vs . 30); pectoral‐fin length 15.0%–15.9% L S ( vs . 14.3); pelvic‐fin length 13.5% L S ( vs . 16.4) and a different morphology of the male copulatory organ. Pseudogilbia australis sp. nov. is the only dinematichthyid so far recorded in the South Atlantic. An updated diagnosis for the genus is also provided.